Ellen Tebbits - Cleary, Beverly; Darling, Louis (New York : Avon, 1990)
Third-grader Ellen takes dancing lessons, wears braces on her teeth, and has a best friend.
4.9
3-6
3-6
Wilson's Children
Elem. School Library Collection
Booklist
Keywords: Schools -- Fiction; Friendship -- Fiction; School stories; Friendship -- Fiction